2003
DOI: 10.1086/377183
|View full text |Cite
|
Sign up to set email alerts
|

Mannose‐Binding Lectin Polymorphisms in Clinical Tuberculosis

Abstract: Mannose-binding lectin (MBL) mediates protection against infections by using the complement system, but certain microorganisms may increase infectivity by exploiting this host defense system. Thus, it has been speculated whether genetically determined low MBL levels may confer partial protection against certain intracellular microorganisms, such as Mycobacterium tuberculosis. We investigated MBL alleles in 109 culture-positive human immunodeficiency virus-uninfected patients with tuberculosis living in Denmark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
110
3
7

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(125 citation statements)
references
References 40 publications
5
110
3
7
Order By: Relevance
“…Interestingly, we also found that the MBL2 genotypes known to result in the highest serum levels of MBL, are associated with susceptibility to CAP caused by obligate intracellular pathogens, such as C. burnetii , M. pneumoniae and Legionella species. This finding is in line with the observation that MBL deficiency can confer protection against infection with mycobacteria, whose pathogenicity also relies on their capacity to grow and/or survive within cells 41, 42. It has been suggested that this mechanism is the main reason why MBL2 polymorphisms are well preserved throughout evolution.…”
Section: Discussionsupporting
confidence: 86%
“…Interestingly, we also found that the MBL2 genotypes known to result in the highest serum levels of MBL, are associated with susceptibility to CAP caused by obligate intracellular pathogens, such as C. burnetii , M. pneumoniae and Legionella species. This finding is in line with the observation that MBL deficiency can confer protection against infection with mycobacteria, whose pathogenicity also relies on their capacity to grow and/or survive within cells 41, 42. It has been suggested that this mechanism is the main reason why MBL2 polymorphisms are well preserved throughout evolution.…”
Section: Discussionsupporting
confidence: 86%
“…Although it is speculative as to what influences have contributed to the preservation of heterozygosity in exon 1, it is likely that changes in the circulating level of higher-order oligomers and the function of variant protein could have a selective advantage in response to environmental pressures. Previous studies have suggested that heterozygotes for B, C, and D could be protected against severe tuberculosis infection (Soborg et al 2003); therefore, MBL2 deficiency could provide protection against pathogens. Moreover, it is likely that lower levels of functionally active higher-order oligomers, resulting from the structural gene variation at codon 54, could serve to reduce the deleterious effects of excessive complement activation via the lectin complement pathway (Takahashi et al 2002) hence the hypothesis that in parasite-infested endemic regions, including India, heterozygosity in the MBL2 gene could have a selective advantage.…”
Section: Discussionmentioning
confidence: 99%
“…Already, preliminary studies have suggested that heterozygotes for B, C or D could be protected against severe tuberculosis infection. 25,95,96 It is also possible that lower MBL serum levels could serve to reduce the deleterious effects of excessive complement activation via the lectin pathway. 97 In our data, we have surveyed the common variants in MBL2 and observed evidence for a high degree of heterozygosity across the gene, yet a restricted number of haplotypes in each of the two blocks.…”
Section: Genes and Immunitymentioning
confidence: 99%
“…The high incidence of heterozygosity for the structural variants in many populations throughout the world 9,10 suggests that there may be a selective advantage for heterozygotes; moreover, individuals heterozygous for B, C and D may be protected against certain pathogens, especially intracellular microorganisms (ie, Mycobacteria spp and Leishmania spp. [21][22][23][24][25][26][27] The fact that there are only seven common haplotypes (eg, HYPA, HYPD, LXPA, LYPA, LYPB, LYQA and LYQC) further supports the role for recent selective pressure on MBL2. MBL deficiency, measured as low serum levels, has been associated with susceptibility to infection in children and adults.…”
mentioning
confidence: 99%